The Roman Senate at War: A Study of Senatorial Government and Administration during the Second Punic War, 218-201 BC BCE - Ballard, Ross (School of Languages and Literatures, 2024)
It is readily accepted that throughout of the third and second centuries, the midRepublican Roman Senate became an increasingly significant body within the political framework of the Republican state. However, little attention has been paid to the effect the devastating and crisis-inducing Second Punic War (218-201 BCE) had upon this political, social, and institutional shift. Thus, this thesis will address the extent to which the military and political responsibilities required of the Senate during the war propelled it to a position of enhanced and accepted prominence. More specifically, it will be argued that the Senate's response to the strains of the Hannibalic war precipitated a distinct centralization of key military affairs of state under the authority of the collective Senate. The primary historical sources that will be used in this thesis are the literary texts for the period in question, most prominently the histories of Polybius and Livy, with supplementary accounts by Appian, Cassius Dio (and Zonaras), Plutarch, and Valerius Maximus. These literary accounts (together with any relevant epigraphic evidence) will be carefully cited, discussed, and analysed to form a positivist, empirical, and evidence-based inquiry into the period in question. Aside from demonstrating that the Hannibalic war did decidedly increase the military and political role of the Senate within the political culture of the Republic, the most promising conclusion drawn from this thesis is that the conflict, and in particular the significant losses in battle amongst the Republican elite, resulted in the firm establishment of the consulares social type, and the political domination of the Senate by senior consulares which would continue well into the second century BCE.